Niger : First Review under the Extended Credit Facility Arrangement-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Niger's First Review Under the Extended Credit Facility Arrangement. Despite security challenges and unfavorable commodity prices, economic performance of Niger has been satisfactory against the backdrop of a good crop season, with real GDP growing by 5 percent in 2016 while inflation remained contained at 0.2 percent. Growth is expected to reach 5.2 percent in 2017, mainly on the back of strengthening hydrocarbon and services sectors, and robust credit growth. The current account deficit will likely decline to 13.4 percent of GDP, reflecting rising exports of oil products, a rebound in uranium exports, and the winding down of import-intensive infrastructure projects.